Electrical resistivity survey combining multiple electrode arrays applied to the studies of underground dams (International Journal of Geoscience, Engineering and Technology, 2020)
Groundwater resources are of paramount importance in sustainable economic development in semiarid regions, such as that in municipally of Jenipapo de Minas, southeast Brazil. The focus of the present work is on realization of geophysical studies using merged electrode arrays in the same profile to study the site suitable for the construction of underground dam in the Bolas Stream bed. The measurements were made along a profile cutting across that local intermittent stream bed. A combining multiple electrode arrays was applied in the profile survey to increase the input data. The results obtained indicate that the subsurface lithologic sequences of the study area are characterized by low resistivity soil layers (> 800Ωm) overlying basement rocks of higher resistivity (> 1000Ωm). There seems to be no fractures or seepages in the basement rock of the Bolas stream bed. In other hand, in the left bank of the stream was identify a conductivity anomaly that could be caused by a fractured in the crystalline rock. However, there is no connection between with the anomaly with the stream bed. The results of merged multiple electrode arrays in the single profile has been found to be useful in understanding the characteristics of resistivity profiles. Thus, the results indicate the surveyed site as a potential for the construction of underground dam in the study area.